Valproate (VPA)-Associated Hepatotoxicity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The metabolic pattern of VPA in 170 epileptic patients without symptoms or signs of hepatic side effects was compared to that in 11 patients with early symptoms and signs of hepatotoxicity and in 5 children with fulminant liver failure.